2018
DOI: 10.3892/etm.2018.6868
|View full text |Cite
|
Sign up to set email alerts
|

Carotid thickness and atherosclerotic plaque stability, serum inflammation, serum MMP‑2 and MMP‑9 were associated with acute cerebral infarction

Abstract: Correlations of carotid intima-media thickness (IMT), atherosclerotic plaque stability, serum inflammatory factors and serum matrix metalloproteinase (MMP)-2 and MMP-9 levels with the condition of disease in patients with acute cerebral infarction were analyzed to explore the predictive value of these risk factors. A total of 56 patients diagnosed with acute cerebral infarction in Jingmen First People's Hospital from February 2016 to January 2017 were selected and divided into the plaque stability group (n=25)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Plaque stability was measured based on the nature of echo in ultrasound. Low-level or equal-level echo indicated unstable plaque, while high-level echo indicated stable plaque [20].…”
Section: Carotid Artery Colour Doppler Ultrasoundmentioning
confidence: 99%
“…Plaque stability was measured based on the nature of echo in ultrasound. Low-level or equal-level echo indicated unstable plaque, while high-level echo indicated stable plaque [20].…”
Section: Carotid Artery Colour Doppler Ultrasoundmentioning
confidence: 99%
“…In China, 110 out of every 100,000 people suffer from cerebral infarction, accounting for 60-80% of stroke patients ( Yong et al., 2013 ). Overexpressed inflammatory cytokines, such as interleukin 6 (IL-6) and high-sensitivity C-reactive protein (hs-CRP), have a great influence on the occurrence and development of ACI patients ( Chen et al., 2018 ). Infusion of recombinant tissue plasminogen activator (rt-PA) is ACI’s only recognized effective therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the association between serum matrix metalloproteinase-9 (SMMP9) in patients with ACI. [ 10 12 ] Despite several studies have explored the effect of hirudin on SMMP9 in patients with ACI, [ 13 – 25 ] no systematic review has evaluated the effect of hirudin on SMMP9 in ACI. Thus, the aim of this study is to assess the effect of hirudin on SMMP9 in patients with ACI.…”
Section: Introductionmentioning
confidence: 99%